Gas chromatographic analysis of in situ cyclitol utilization by Klebsielleae growing in redwood extracts. - Talbot, H W (1979)
Gas chromatographic analysis was employed to demonstrate in situ cyclitol utilization in aqueous extracts of redwood by isolates of Klebsiella, Enterobacter, and several other genera of gram-negative bacteria. In aqueous redwood extracts, all but one of the Klebsiella and Enterobacter isolates tested reached densities exceeding 5.0 x 10(6) cells/ml within 4 days, and all utilized pinitol and sequoyitol. Other enteric bacteria did not utilize cyclitols in this extract. A defined minimal medium, containing the carbohydrates and cyclitols (including myo-inositol) in redwood, was used to determine which carbon sources are preferentially utilized by Klebsielleae and other bacteria. It was found that D-glucose and L-arabinose were consumed by Klebsiella before the three cyclitols were utilized. Pinitol utilization proceeded in more slowly than that of sequoyitol and myo-inositol. Cyclitol utilization in the defined medium was also observed for Yersinia, Erwinia, and Salmonella. Escherichia coli isolates did not utilize cyclitol compounds. The ability to use cyclitols as a sole source of carbon can explain the high cell densities of Klebsielleae in redwood water reservoirs and in redwood lumber.